Recurrent Episodes of Dissociative Fugue with Comorbid Severe Depression and Alcohol Dependence Syndrome - Daliri, Dennis Bomansang; Afaya, Agani; Koomson, William H. F.; Akatibo, Emmanuel (Case Reports in Psychiatry, 2022)
The rarity and close resemblance to other mental health conditions of dissociative fugue make it difficult to diagnose. Akin to a culture-bound syndrome, most African countries have their local explanation for this unique presentation and therefore people may not seek evidence-based health care but rather may resort to faith-based-treatment which may not give the best results. This is the case of a 39-year-old man who has experienced about five episodes of dissociative fugue over nine years. This case points out the comorbidities associated with the condition. We report this case to increase awareness of the condition and to bring to the fore the need for further studies into psychopathology and the treatment modalities.